Tantangan Pengelolaan Pendidikan di Sekolah Dasar: Peran Humas dalam Mengatasi Ketimpangan Partisipasi Masyarakat Terhadap Pembelajaran - Syaharani, Adinda Regita; Faradila, Esla Zahra; Nababan, Indah Intansari; Hafiza, Nadyne Dinda; Awaliyah, Novia Aliestiani; Prihatini, Prihatini (Indo-MathEdu Intellectuals Journal, 2025)
Education management in primary schools faces a major challenge in involving the community as an integral part of the learning process. The gap in community participation in primary school education is a major challenge in improving the quality of learning. This study aims to analyze the role of public relations as a liaison between schools and communities in overcoming this gap. The research was conducted through a literature review method by analyzing various relevant scientific sources. The study evaluates the role of public relations as a communication bridge between schools and communities to effectively convey educational information and encourage active community involvement in school activities. The results show that PR plays an important role in creating harmonious relationships between schools and communities through two-way communication strategies, the use of digital technology and the promotion of school programs. The implications of this study emphasize the importance of training public relations personnel and providing infrastructure to support inclusive and sustainable education management